1968
DOI: 10.1172/jci105870
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neomycin on exchangeable pools of cholesterol in the steady state

Abstract: A B S T R A C T Five patients received cholesterol7a-3H intravenously during control periods. Specific activity of total serum cholesterol was determined serially during the 1st wk and weekly thereafter. 28-59 wk after the injection of the tracer, when no further radioactivity could be detected in serum cholesterol, 2 g of oral neomycin was given daily to four patients for the remainder of the experiment. Average total serum cholesterol concentrations were reduced by 20, 21, 26, and 29%, respectively, in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

1973
1973
1994
1994

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…1 (14). Thus, in the neomycin period, the cholesterol balance represents the difference between intake and the sum of cholesterol synthesis plus cholesterol efflux from tissue stores.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 (14). Thus, in the neomycin period, the cholesterol balance represents the difference between intake and the sum of cholesterol synthesis plus cholesterol efflux from tissue stores.…”
Section: Methodsmentioning
confidence: 99%
“…Two previous studies have indicated that neomycin causes increased fecal excretion of neutral and acidic steroids (11,12), whereas another observed increased bile acid excretion only (13). In 1968 Samuel, Holtzman, Meilman, and Perl (14), using isotope kinetic techniques, showed that the administration of neomycin resulted in a decrease in the size of tissue pools of cholesterol.…”
Section: Introductionmentioning
confidence: 99%
“…It is not, however, known whether large neomycin doses could also increase fecal bile acid output; whether the neomycin-induced increase in fecal steroids is long-standing, as the serum cholesterol lowering is; whether the decrease in serum cholesterol is related to changes in cholesterol elimination; and whether cholesterol synthesis is compensatorily increased by the drug. Cholesterol turnover studies off and on neomycin did not reveal any significant changes in the half time of the serum cholesterol radioactivity decay curve (14), and the unchanged slope of this curve during the neomycininduced fall in serum cholesterol was interpreted to be a result of the combined action of reduced absorption, enhanced mobilization oftissue cholesterol and stimulated cholesterol synthesis (13).…”
mentioning
confidence: 97%
“…INTRODUCTION Considerable information is now available about the turnover of plasma cholesterol in normal and in hyperlipidemic humans. When kinetic studies are conducted for periods of about 10-12 wk, the turnover of cholesterol can be described satisfactorily by a simple twopool model (1)(2)(3)(4). This model has been used to examine the relationships between some parameters of cholesterol metabolism and other clinical features such as body weight (3).…”
mentioning
confidence: 99%
“…This model has been used to examine the relationships between some parameters of cholesterol metabolism and other clinical features such as body weight (3). The kinetic approach has also been employed to assess the effects of drugs that lower serum lipids, such as cholestyramine resin (1,5,6), neomycin (2), and clofibrate (7). The effects of ileal bypass surgery on body cholesterol metabolism have been examined by the turnover technique (6,8).…”
mentioning
confidence: 99%